Collective imaginaries of caring landscapes for rural youth: a concept mapping study in northern Sweden - Frida Jonsson (BMC, 2021)
Abstract Background In the current study, the approach of ‘utopia as method’ was combined with the concept ‘landscapes of care’ to explore collective imaginaries of caring landscapes in relation to young people living in rural northern Sweden, while focusing specifically on what such landscapes should ideally look like, and how various strategies could help to realise the visions. Methods The research was conducted using a modified concept mapping methodology comprising three phases of data collection and analysis. This facilitated the integration of tacit knowledge and utopian visions of young people, professionals and policymakers living and working in various parts of northern Sweden. Results The results indicated that caring landscapes should: ‘provide services responsive to young people’s wishes and needs’, ‘be organised around values of safety, equity and youth participation’, and ‘rework metro-centredness’ in order to care for, with and about rural youth. Conclusions The findings can be viewed as an imaginary reconstitution of communities in rural northern Sweden, but also as hypothetical building blocks to be used for developing caring landscapes and a ‘good countryside’ where young people have the possibility to live a good life in decent health.